Potential alternatives with vegetable extracts in control of tomato early blight - Almeida, Edvan Nilson de; Moura, Gabriela Silva; Franzener, Gilmar (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The objective of this study was to evaluate the antifungal potential of three species of medicinal plants: Zingiber officinale (ginger), Allium sativum L. (garlic) and Caryophyllus aromaticus L. (clove) in vitro and in vivo, for the control of the pathogen Alternaria solani, causal agent of the black pint. Mycelial growth, spore germination and germination size of A. solani were evaluated in vitro at concentrations of 1.0, 5.0, 10, 15 and 20%. For the in vivo evaluation of tomato seeds cv. Santa Cruz Kada were seeded in styrofoam trays of 200 cells containing commercial substrate. After 30 days the seedlings were transplanted to 5 L pots containing soil and kept in a greenhouse. The treatments for the in vivo assay were aqueous extract of ginger, garlic and clove at 20% concentration. The applications were started after 47 days of transplanting the greenhouse, being carried out once a week until the time of harvest. Evaluations of the area under the disease progress curve (AACPD), mean number and fruit weight were performed. The experiments were conducted in a completely randomized design with five replicates. Clove, garlic and ginger extracts showed a direct inhibitory effect on the fungus and reduced the AACPD in 55.8, 29.5 and 22.5% in relation to the control water, respectively. These results indicate the potential of the extracts evaluated in the control of the black peat of tomato, with emphasis on clove extrac.